2022
DOI: 10.3390/jcm11051248
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Anti-SARS-CoV-2 Vaccines: Vigilance Is Still Required

Abstract: The opinion I put forward in this paper is that attention must continue to be paid to clinical observations compatible with a detrimental effect of anti-SARS-CoV-2 in certain diseases of immunological nature. Using the example of the atypical thrombocytopenic thromboses caused by adenoviral-vector-based vaccines, I argue that usual post-marketing pharmacovigilance programs may fail in identifying very rare vaccine-related disorders. Since the robust protective immunity induced by mRNA vaccines is related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, the vaccination is inevitably associated with an induction of a systematic immune response that might result in rare immune-mediated complications. 8 , 12 , 22 Concerns about vaccination-induced graft rejection have previously been raised among solid organ transplant recipients. 9 This issue has been addressed several times in various vaccines in the past, and no conclusive evidence of an increased risk of rejection or graft loss has been found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the vaccination is inevitably associated with an induction of a systematic immune response that might result in rare immune-mediated complications. 8 , 12 , 22 Concerns about vaccination-induced graft rejection have previously been raised among solid organ transplant recipients. 9 This issue has been addressed several times in various vaccines in the past, and no conclusive evidence of an increased risk of rejection or graft loss has been found.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Similar concerns have been raised with the advent of new mRNA vaccines. 12 Because mRNA vaccination is a novel technology whose safety has not yet been comprehensively studied in KTRs, establishing its safety regarding alloreactive adverse events is important. Thus, further research of vaccine responses in KTRs is invaluable because it not only provides insights into unexpected impacts of immunosuppression on infections and immunization responses but can also bring important postmarketing safety data and information about long-term vaccine effectiveness and antibody durability.…”
mentioning
confidence: 99%
“…For instance, there are T follicular helper (Tfh) cells that are needed for both maintenance and normal development of germinal centers ( 168 ) and also play an essential role in some malignancies and autoimmunities ( 169 ). Since a study performed by Pardi et al ( 168 ) revealed that lipid-encapsulated nucleoside modified vaccines could trigger a robust Tfh cells hyperactivation, it can be possible to link the lymphoma relapse in the cases mentioned above with the Tfh cells hyperactivation caused by mRNA-based COVID-19 vaccines ( 168 , 170 ). In a recent report, a case of angioimmunoblastic T cell lymphoma (AITL) developed a rapid progression after the booster dose of the BNT162b2 vaccine ( 171 ).…”
Section: Lymphadenopathymentioning
confidence: 99%
“…A s the protection provided by 2 doses of an mRNA vaccine substantially wanes over time and with the emergence of new viral variants, 1 administration of booster doses was recommended for kidney transplant recipients (KTRs). [2][3][4] Vaccination-associated immune activation might be associated with allorecognition and graft injury, 5 and safety data in KTRs are insufficient.…”
mentioning
confidence: 99%